Perspektif Baru dalam Proses Penyebaran Islam di Kerajaan Bone Sulawesi Selatan Indonesia pada Abad ke 17 - Rahmawati Rahmawati (Universitas Islam Negeri Alauddin Makassar, 2015)
The purpose of this research is to observe the new perspective in spreading Islam in Bone Kingdom on 17th century. There are a lot of discourses in historian’s arguments about when Islam firstly appeared in Nusantara, especially in South Celebes. Based on a fact, Islam was brought by clerics from Minangkabau i.e. Datu ri Bandang, Datu Patimang dan Datu Itiro. In spite of the fact was talking about islamization process in South Celebes which was brought by clerics, we will found that Bone Kingdom had a different condition. Bone in fact, had accepted Islam after joined in a war, named Musu Asselleng (The war of Islamization). The result of that war, Bone had accepted Islam after defeated by Gowa Kingdom in 1611.